Behavior of fire damaged concrete cylinders with carbon fibre reinforced polymer wrap under monotonic compression - Prasad, Y. K. Guru; Ramaswamy, Ananth (Journal of Structural Engineering, 2024)
This paper examines the stress-strain response of normal strength concrete cylinders (25MPa and 35MPa 28 day cylinder compressive strength) 150mm in diameter and 300mm in height, that have been exposed to temperatures of 715 deg C for a duration of 4 hours and 2 hours, 550 deg C for a duration of 4 hours and 425 deg C for a duration of 4 hours and are wrapped with CFRP after cooling and subjected to increasing monotonic compressive loads to assess the effi cacy in repair of fire damaged concrete. The concrete cylinders, which were subjected to fire damage at different temperatures as indicated above, were cooled, and wrapped with a single layer of carbon fibre reinforced polymer fabric using an epoxy binder. It was observed that the concrete cylinders subjected to damage due to exposure at higher temperatures (715 deg C for 4 hours and 2 hours and 550 deg C for 4 hours) without CFRP wrap had cracked extensively and had a very low compressive strength of about 12 to 50 % of the strength of corresponding control cylinders under uniaxial compression. When similar thermally damaged cylinders after cooling in air were wrapped with CFRP, and were then subjected to monotonic uniaxial compressive loading, the failure loads increased substantially.